Images at War : Illustrated Periodicals and Constructed Nations - Martin, Michele, 1944- (Book collections on Project MUSE., 2006)
"Using the press coverage of the Franco-Prussian war as a starting point, Michele Martin's Images at War examines nineteenth-century illustrated periodicals published in France, Germany, England, and Canada (with references also to Italy and the United States), and argues that during that era they worked to reinforce particular national identities." "The images that appeared played an essential role in how the concept of nationalism was expressed and reproduced, usually by pitting cultures and countries against one another. These illustrated periodicals helped to shape nations where nations had not previously existed - such as Germany, Italy, and Canada, which were only just coming into their own as states. In war, Martin observes, these documents also represented a non-verbal method of communicating emotionally trying, politically challenging, and oftentimes contradictory information to the public, literate and non-literate alike." "The history of nineteenth-century illustrated papers underscores their legitimacy as a form of journalism. They were more than a commodity produced for profit; they offered serious reflection and commentary designed by editors to have specific effects on the readers. Images at War is a study of this early news medium and its part in the construction of nationalism in the midst of war."--Jacket.